PERENCANAAN STRUKTUR BETON BERTULANG PADA BANGUNAN WATCHROOM PKP-PK DENGAN SISTEM RANGKA PEMIKUL MOMEN KHUSUS DI BANDAR UDARA KELAS I UTAMA JUWATA-TARAKAN - Rizal Afandi; Bambang Wasito; Ranatika Purwayudhaningsari (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Watchroom or monitoring room is one of the facilities at an airport to visually monitor aircraft movements. In connection with this, at Juwata Tarakan Class I Main Airport there is a watchroom with a location that is not yet strategic so it must be moved according to the existing master plan. In this final project, it is intended to plan a watchroom structure in accordance with SNI. From the results of the analysis, the watchroom construction site is categorized as risk D so that in the structural analysis the SRPMK (Special Moment Resistant Frame System) method is used. In the calculation of the structure, the concept of Strong Column and Weak beam is used, which refers to SNI 1726:2019 regarding earthquakes. In planning the building structure, SNI 2847:2019 regarding reinforced concrete and SNI 1727:2018 is used for loading. In this final project, SAP 2000 is used for building 3D modeling, spColumn for calculation of column interaction diagrams, and Autocad 2016 for reinforcement details. From the results of the structural design, the dimensions of the child beams are 300/250, the main beam is 400/300, the column is 400/400 and the plate thickness is 130 mm and the structural reinforcement details are included in the technical drawings. In addition, in checking the control design of the watchroom structure based on SNI 1726:2019, it has fulfilled the requirements and fulfilled the Strong Column Weak Beam concept where the value of Mnc = 314.7 kNm ≥ 1.2 Mnb = 226.272 kNm, so the watchroom structure has high ductility.